Glucose-6-phosphate dehydrogenase (G6PD)-deficient infants: Enzyme activity and gene variants as risk factors for phototherapy in the first week of life - Wong, FL; Ithnin, A; Othman, A; Cheah, FC (Wiley, 2024)
Indexed by WOS/ Scopus